Prospective case‐controlled sound localisation study after cochlear implantation in adults with single‐sided deafness and ipsilateral tinnitus. (9th February 2016) - Mertens, G.; Desmet, J.; De Bodt, M.; Van de Heyning, P.
Abstract : Objectives: To analyse the sound localisation skills of subjects with profound single‐sided deafness (SSD) and accompanied ipsilateral tinnitus who are using a cochlear implant (CI) for between 4 and 11 years. Design: Sound localisation skills were tested using nine loudspeakers in a frontal semicircle ranging from −90° to +90°. Subjects were tested in the CION and the CIOFF conditions via 3 localisation stimuli: broadband noise (BB), low‐pass noise (LP) and high‐pass noise (HP). Participants: The test group consisted of 10 adult subjects with profound sensorineural SSD, ipsilateral tinnitus and a CI. Normative data of a control group of 30 normal hearing subjects were used for comparison. Main outcome measures: Sound location accuracy was analysed via the root‐mean‐square error (RMSE), the mean absolute error (MAE), the localisation bias (' b' ) and the bias‐adjusted deviation (' d b ' ). Subjective dynamic aspects of hearing were assessed via a reduced version of the Speech, Spatial and Qualities of Hearing Scale (SSQ5 ). Results: For all 3 stimuli, the RMSE improved significantly in SSD subjects in the CION condition compared to the CIOFF condition. The localisation accuracy of subjects with SSD improved significantly for BB and HP stimuli. A significant bias‐adjusted deviation 'd b ' was found for the BB and HP stimuli. Subjects' mean SSQ5 scores were significantly higher in the CION condition at test date than in the CIOFF condition preoperatively. Conclusions: Subjects can better locate sound in the CION condition than in the CIOFF condition.